2017
DOI: 10.1037/pag0000178
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in emotion recognition: A question of modality?

Abstract: Previous research has suggested age deficits in unimodal emotion recognition tasks. In 2 studies with independent samples, we tested the idea that older adults' performance will be enhanced in multimodal emotion recognition tasks. In each study, participants were presented with newly developed film clips, each portraying a young or an old woman while she relived an emotional memory. As a first step, participants received the film clips in each of 3 unimodal conditions (facial, lexical, prosodic). As a second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
2
27
3
Order By: Relevance
“…Rather, when only considering the intact conditions, there was no significant age group by condition interaction, indicating that the difference in accuracy remained roughly the same across A, V, and AV conditions. Therefore, unlike what has been previously reported 122,151 , we find that older participants are as good as younger participants at integrating auditory and visual information, but not better. Wieck and Kunzmann 151 already proposed that divergent findings could be due to differences in the quality of the emotion expression.…”
Section: Older and Younger Adults Integrate Audiovisual Information For Emotion Recognition Similarlycontrasting
confidence: 99%
See 3 more Smart Citations
“…Rather, when only considering the intact conditions, there was no significant age group by condition interaction, indicating that the difference in accuracy remained roughly the same across A, V, and AV conditions. Therefore, unlike what has been previously reported 122,151 , we find that older participants are as good as younger participants at integrating auditory and visual information, but not better. Wieck and Kunzmann 151 already proposed that divergent findings could be due to differences in the quality of the emotion expression.…”
Section: Older and Younger Adults Integrate Audiovisual Information For Emotion Recognition Similarlycontrasting
confidence: 99%
“…Overall, we found that while ageing leads to a general decline in emotion recognition 148,149 , it does not have an effect on audiovisual integration abilities. Contrary to the findings from Chapter 4, it has been proposed that audiovisual integration is enhanced in ageing, both in general, for example for stimulus detection or localization, but also for speech recognition 177,178 and in particular for emotion perception 122,151 .…”
Section: Ageing Leads To a General Decline In Emotion Recognition But Does Not Reduce Integration Or Compensation Abilitiesmentioning
confidence: 70%
See 2 more Smart Citations
“…In our experiment, due to the large number of different emotions included, the emotional cues in each modality may have been subtler and more complex than in previous studies, such that integrating auditory and visual cues does not necessarily resolve all ambiguity. The chance of that happening is much smaller when there are fewer emotions being portrayed; Wieck and Kunzmann (2017) only presented two emotions (anger and sadness), and Hunter et al, presented four (fear, sadness, disgust, and anger). In our study, in contrast, 12 emotions (of which six were negative) were used, and some were closely related (e.g., anger and irritation).…”
Section: Older and Younger Adults Integrate Audiovisual Information For Emotion Recognition Similarlymentioning
confidence: 99%